Scaffolding peer-assessment skills: Risk of interference with learning domain-specific skills?. (April 2019) - Könings, Karen D.; van Zundert, Marjo; van Merriënboer, Jeroen J.G.
Abstract: Giving students complex learning tasks combined with peer-assessment tasks can impose a high cognitive load. Scaffolding has proven to reduce cognitive load during learning and improve accuracy on domain-specific tasks. This study investigated whether scaffolding has a similar, positive effect on the learning of peer-assessment tasks. We hypothesised that: (1) domain-specific scaffolding improves domain-specific accuracy and reduces time on task and perceived mental effort, and (2) peer-assessment scaffolding improves peer-assessment accuracy and reduces time on task and perceived mental effort. Additionally, we explored whether there was an interaction between domain-specific and peer-assessment scaffolding. In a 2x2 experiment with the factors domain-specific scaffolding (present, absent) and peer-assessment scaffolding (present, absent), 236 secondary school students assessed the performance of fictitious peers in an electronic learning environment. We found that domain-specific accuracy indeed improved with domain-specific scaffolding, confirming our first hypothesis. Our tests of the second hypothesis, however, revealed surprising results: peer-assessment scaffolding significantly increased accuracy and mental effort during learning, it had no effect on peer-assessment accuracy at the test and led to reduced domain-specific accuracy, even when combined with domain-specific scaffolding. These results suggest that scaffolding students' peer assessment before they have mastered the task at hand can have disturbing effects on students' ability to learn from the task. Highlights: Domain-specific accuracy suffers from peer-assessment scaffolding. When learning complex tasks, peer-assessment scaffolding increases cognitive load. For new tasks, peer-assessment scaffolding is not as effective as domain-specific scaffolding. Peer-assessment scaffolding may best be applied after mastery of domain-specific skills.